Which Trauma Treatment Suits me? Identification of Patients' Treatment Preferences for Posttraumatic Stress Disorder (PTSD) - Schwartzkopff, Laura; Gutermann, Jana; Steil, Regina; Müller-Engelmann, Meike (Frontiers in Psychology, 2021)
Several psychotherapy treatments exist for posttraumatic stress disorder. This study examines the treatment preferences of treatment-seeking traumatized adults in Germany and investigates the reasons for their treatment choices. Preferences for prolonged exposure, cognitive behavioral therapy (CBT), eye movement desensitization and reprocessing (EMDR), psychodynamic psychotherapy and stabilization were assessed via an online survey. Reasons for preferences were analyzed by means of thematic coding by two independent rates. 104 traumatized adults completed the survey. Prolonged exposure and CBT were each preferred by nearly 30%, and EMDR and psychodynamic psychotherapy were preferred by nearly 20%. Stabilization was significantly less preferred than all other options, by only 4%. Significantly higher proportions of patients were disinclined to choose EMDR and stabilization. Patients who preferred psychodynamic psychotherapy were significantly older than those who preferred CBT. Reasons underlying preferences included the perceived treatment mechanisms and treatment efficacy. Traumatized patients vary in their treatment preferences. Preference assessments may help clinicians comprehensively address patients’ individual needs and thus improve therapy outcomes.